Mental Health Among School-Going Adolescents in Greater London: A Cross-Sectional Study - Al-Zawaadi, Asmaa; Hesso, Iman; Kayyali, Reem (Frontiers in Psychiatry, 2021)
Objectives: Mental health problems are among the leading causes of health-related disability among children and adolescents worldwide. However, there is still a global challenge in terms of gathering consistent epidemiological information about the issue. The present study was designed to describe various mental health issues and factors associated with negative feelings among adolescents in Greater London. Methods: This is a cross sectional study, using a self-administered questionnaire (Cronbach’s alpha=0.742). A convenience sampling strategy was used to recruit participants who were school/college attending adolescents, aged 11-19. A minimum sample size of 199 was required (95% confidence interval, 5% margin of error and 15.3% population proportion). The study was conducted between February and April 2016 in Greater London. Descriptive statistics and inferential statistics including chi square, spearman correlation and binary logistic regression were used to identify the key findings. Data analysis was performed using SPSS v21. Results A total of 526 out of 1920 surveys were collected across 18 secondary schools and two colleges, giving a response rate of 27.4%. More than half of the adolescents reported to be either neutral (41.4%), sad (7.8%) or very sad (2.8%), whereas 48% reported to be either happy (35%) or very happy (13%). Difficulties in relationships and hectic schedules were among the most stressful situations affecting adolescents’ mental health. Discrimination was identified as the main predicting factor with five folds increase in odds of having negative mental health symptomatology. Other significant risk factors identified were age, gender, smoking and health co-morbidities. Conclusion Discrimination was identified as the most predictive factor influencing negative symptomology among the study cohort. The study had several limitations, most notably the use of a non-validated surrogate measure for mental health, in addition to the exclusion of adolescents aged 10-11 years, school/college dropouts and non-school going adolescents. A similar study on a national scale is highly recommended to determine the real magnitude of the problem, which would be the starting point towards proper tackling of mental health issues and associated complexities among the adolescent population across England.